2009
DOI: 10.1088/0004-637x/695/2/988
|View full text |Cite
|
Sign up to set email alerts
|

The Cepheid Period-Luminosity Relation (The Leavitt Law) at Mid-Infrared Wavelengths. Ii. Second-Epoch LMC Data

Abstract: We present revised and improved mid-infrared Period-Luminosity (PL) relations for Large Magellanic Cloud (LMC) Cepheids based on double-epoch data of 70 Cepheids observed by Spitzer at 3.6, 4.5, 5.8 and 8.0 µm. The observed scatter at all wavelengths is found to decrease from ±0.17 mag to ±0.14 mag, which is fully consistent with the prediction that the total scatter is made up of roughly equal contributions from random sampling of the light curve and nearlyuniform samplings of stars across the instability str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(89 citation statements)
references
References 8 publications
9
78
2
Order By: Relevance
“…This is the first such work primarily because the requisite observational data have not existed previously. Since the farther reach of (brighter) Cepheid PL relations makes their study potentially more influential, the Spitzer Space Telescope has been used to derive mid-infrared PL relations for Galactic (Marengo et al 2010) and Magellanic Clouds (Madore et al 2009) Cepheids (the latter making use of SAGE survey data: Meixner et al 2006;Madore et al 2009). These studies of Galactic (Magellanic Clouds) Cepheid midinfrared PL relations reported best-fit dispersions of ∼0.2 mag (∼0.12 mag).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first such work primarily because the requisite observational data have not existed previously. Since the farther reach of (brighter) Cepheid PL relations makes their study potentially more influential, the Spitzer Space Telescope has been used to derive mid-infrared PL relations for Galactic (Marengo et al 2010) and Magellanic Clouds (Madore et al 2009) Cepheids (the latter making use of SAGE survey data: Meixner et al 2006;Madore et al 2009). These studies of Galactic (Magellanic Clouds) Cepheid midinfrared PL relations reported best-fit dispersions of ∼0.2 mag (∼0.12 mag).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely, as indicated in recent work from Spitzer data, that mid-infrared Cepheid PL relations are even superior to their near-infrared relations because of their even lower sensitivity to reddening, and lower intrinsic dispersions (Madore et al 2009). Yet, their dependence on metallicity has still to be investigated and they cannot be exploited from the ground making them exceedingly expensive to use.…”
Section: Discussionmentioning
confidence: 93%
“…The expected MIR P-L slopes are represented as dashed lines in this Figure, and suggest that the P-L slopes approach these asymptotic values around ∼ 1.5µm. Empirical IRAC band P-L slopes from Madore et al (2009b) were included for comparison.…”
Section: The Empirical Mid-infrared P-l Relationsmentioning
confidence: 99%